Evaluasi Kualitas Website Perpustakaan Universitas Brawijaya Menggunakan Metode Webqual 4.0 Dan Importance Performance Analysis (Studi Pada Perpustakaan Universitas Brawijaya) - Ida Fitriah; Satrio Hadi Wijoyo; Bondan Sapto Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Website quality is one of the crucial factors that has a big influence on the image of the organization (library), but it can also affect users which result in user behavior towards services. Major changes in library system requirements also bring high demands or requirements from service users regarding the quality of library information systems. According to Zeithaml in a study by Manasra et.al (2013), a website that offers better performance, including specific quality of a good website will be useful in increasing user satisfaction. This study analyzes user perception and user expectations of the quality of the UB library website using Webqual 4.0 and Importance Performance Analysis (IPA) methods. The results of the measurement of performance and importance show a very good level of conformity between the two with an average percentage of> 85%. However, in the IPA quadrant analysis, the website quality on the U3, U4, IQ11, and SIQ22 indicators cannot meet user expectations. Because the performance value of this indicator is below the average overall performance value. Researchers hope that the results of this research can be used as a reference for the management of the UB library website to improve / improve the quality and answer user expectations of the quality of the website.